1990
DOI: 10.1029/jd095id10p17001
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall and surface kinematic conditions over central Amazonia during ABLE 2B

Abstract: Meteorological and chemical data collected during the wet season Amazon Boundary Layer Experiment near Manaus, Brazil, are used to investigate the rainfall, rainfall systems, and surface kinematics of the central Amazon basin wet season. Analysis of the Geostationary Operational Environmental Satellite (GOES-West) imagery indicates that, based on location of initial development, there are three main types of convective systems which influence a mesoscale network near Manaus. Coastal Occurring Systems (COS) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
0
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 18 publications
(7 reference statements)
6
90
0
15
Order By: Relevance
“…The ABLE-2 project consisted of two expeditions: the first in the Amazonian dry season (ABLE-2A) during July-August 1985 and the second in the wet season (ABLE-2B) during April-May 1987 (Harriss et al, 1988. Greco et al (1990) have described the rainfall and kinematics of the central Amazon using GOES (Geostationary Operational Environmental Satellite) imagery, revealing the importance of tropical squall lines in the rainfall regime of the Amazon. Some years later, Garstang et al (1994), Greco et al (1994), and Cohen et al (1995) provided a detailed description of tropical squall lines in the region.…”
Section: Knowledge About Cloud Process In the Amazon Acquired During mentioning
confidence: 99%
“…The ABLE-2 project consisted of two expeditions: the first in the Amazonian dry season (ABLE-2A) during July-August 1985 and the second in the wet season (ABLE-2B) during April-May 1987 (Harriss et al, 1988. Greco et al (1990) have described the rainfall and kinematics of the central Amazon using GOES (Geostationary Operational Environmental Satellite) imagery, revealing the importance of tropical squall lines in the rainfall regime of the Amazon. Some years later, Garstang et al (1994), Greco et al (1994), and Cohen et al (1995) provided a detailed description of tropical squall lines in the region.…”
Section: Knowledge About Cloud Process In the Amazon Acquired During mentioning
confidence: 99%
“…The LI can be clearly identified in GOES images and in the CMORPH data product (Kousky et al, 2006). Greco et al (1990) found that instability line that reached Manaus during ABLE-2B were responsible for 40% of directly observed rainfall. The somewhat reduced nocturnal convective activity still brings appreciable rainfall to the region (Cutrim et al, 2000;Angelis et al, 2004, Kousky et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…O período chuvoso na Amazônia Tropical é iniciado pela influência de Sistemas Sinóticos condicionado pelo aumento da quantidade de umidade na Camada Limite Planetária (CLP) e da diminuição da temperatura no topo, reduzindo a CINE (Greco et al, 1990). Porém, mais de 80% desta precipitação é oriunda de convecção profunda.…”
Section: Introductionunclassified